Indicators of Spiritual Health in the Life of Hazrat Zahra; Guidance for Today's Generation - Rasol Hosiny Masom (Beyhagh)
Background and Aims: The importance of spirituality and human spiritual growth has attracted the attention of health professionals more and more in the past few decades. The progress of science on the one hand and the dynamic and complex nature of societies on the other hand have caused the spiritual needs of human beings to increase and become more important compared to their material demands. On the other hand, the way of life of the Fourteen Innocents and the verses and traditions of those nobles have always been and are a beacon, guiding and enlightening the hearts of Muslims in any situation. There is no doubt that Hazrat Fatima Zahra as a perfect human being and the traditions left by her are a criterion for determining the correctness or incorrectness of any statement regarding various dimensions of health. The purpose of this research is to gain a clearer understanding of spiritual health based on Islamic teachings and compare it with a reliable source for the treatment of disorders in today's society. Materials and Methods: In this study, a review was conducted in SID, Magiran, PubMed, Google Scholar, etc. using the keywords spirituality, spiritual health, spiritual well-being, Hazrat Zahra, fourteen innocents and... were searched in the period of 2013 to 2023. Related articles and articles related to the purpose of the study were extracted. At the end, the obtained results were compared and analyzed with the hadiths and narrations left by that Prophet and spiritual health indicators based on Islamic teachings that were confirmed in previous studies. Result: After conducting studies on spiritual health in reliable Persian and English sources, indicators of spiritual health were classified according to Islamic teachings in five main axes, which include: 1- Creationism 2- Religious rationality 3- Psychological balance 4- Obligation 5- They are apocalyptic. These five characteristics were repeated in various studies in different forms and titles (monotheism, vision, tendency, action, ideas, ethics, Godcenteredness, purposefulness, belief in the unseen world, etc.). It is also possible to compare the introduced axes with the principles and pillars of religion; Creationism = monotheism, eschatology = resurrection, etc, which strengthens the connection between the indicators introduced in this research and the lifestyle of religious leaders. Conclusion: Spiritual health has different definitions due to its highly abstract nature. In this study, the introduced indicators of spiritual health based on Islamic teachings were reconfirmed after comparing with hadiths, traditions and the life style of Hazrat Fatimah.